Correction: Liquid-capped encoded microcapsules for multiplex assays. Issue 4 (27th January 2017) - Song, Younghoon; Jeong, Yunjin; Kwon, Taehong; Lee, Daewon; Oh, Dong Yoon; Park, Tae-Joon; Kim, Junhoi; Kim, Jiyun; Kwon, Sunghoon
Abstract : Correction for 'Liquid-capped encoded microcapsules for multiplex assays' by Younghoon Song et al., Lab Chip, 2017, DOI: ; Web:10.1039/c6lc01268j .